Abundance of badgers (Meles meles) in England and Wales - Johanna Judge (Nature Portfolio, 2017)
Abstract The European badger (Meles meles) is of considerable interest in the UK as it is both a protected species and the main wildlife reservoir for bovine tuberculosis infection in cattle. While there have been three national badger surveys in the 1980s, 1990s and 2011–13, using the number of badger main setts as a proxy for the abundance of badger social groups, none has combined contemporary data on social group size at landscape and national scales. We estimated social group size by genotyping hair samples collected at 120 main setts across England and Wales and employing a capture-mark-recapture method based on genotypes. The estimated mean social group size in England and Wales was 6.74 (±0.63) badgers. There was considerable variation in badger social group size among Land Class Groups (LCGs), with a low of 2.67 in LCG3 and a high of 7.92 in LCG4. Combining these results with the recent Badger Sett Survey of England and Wales, we estimate there are approximately 485,000 badgers (95% confidence intervals 391,000–581,000) in England and Wales. Although direct comparison with previous estimates is not ideal owing to methodological differences, our results are consistent with a marked increase in the badger population of England and Wales since the 1980s.